1994
DOI: 10.1111/j.1540-8159.1994.tb03782.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Pacing Algorithm for Overdrive Suppression of Atrial Fibrillation

Abstract: Constant rapid pacing may suppress arrhythmias, but it is usually poorly tolerated in the long term. We report a pilot study of a new pacing algorithm for overdrive suppression of atrial premature complexes (APCs) and atrial fibrillation (AF), which prevents postextrasystolic pauses and varies the pacing rate in response to the frequency of APCs. The algorithm was tested in a multiple crossover study for 24 hours in dual chamber pacemakers implanted in 70 patients. Comparison was made on ambulatory recordings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 4 publications
1
35
1
2
Order By: Relevance
“…The role of a true overdrive atrial pacing algorithm was first evaluated by Murgatroyd et al, who found that the APP algorithm provides additional benefit. 7 This algorithm allows the pacemaker to maintain a pacing rate slightly higher than the sinus rate. As a result, a high percentage of atrial pacing is achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of a true overdrive atrial pacing algorithm was first evaluated by Murgatroyd et al, who found that the APP algorithm provides additional benefit. 7 This algorithm allows the pacemaker to maintain a pacing rate slightly higher than the sinus rate. As a result, a high percentage of atrial pacing is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial pacing has been shown to prevent paroxysmal AF. [4][5][6][7] Overdrive atrial pacing is thought to prevent AF triggered by bradycardia and premature atrial beats. The Atrial Pacing Preference™ (APP; Guidant, St Paul, MN, USA) algorithm allows the pacemaker to maintain a pacing rate slightly higher than the sinus rate.…”
mentioning
confidence: 99%
“…Moreover, some effects on atrial remodeling, although little in magnitude, have been demonstrated. Other algorithms, such as the Atrial Preference Pacing algorithm (Medtronic, Minneapolis, MN) failed to show any reduction in the number of modeswitching episodes and symptomatic episodes despite a reduction of premature atrial beats [38].…”
Section: Trigger Suppression Algorithmsmentioning
confidence: 99%
“…It is believed that atrial premature contraction will be reduced following by increasing the heart rate. Mugatroyd et al 71) reported that when an algorithm is used to increase the heart rate to 12.5% higher than the previous sinus rhythm at detection of atrial premature contraction by dissolving the resting phase after premature contraction was obtained, atrial premature contraction and the short run of atrial premature contraction were reduced by 69% and 75%, respectively. Unfortunately, no significant reduction of paroxysmal atrial fibrillation could be achieved.…”
Section: Preventative Pacing Algorithms 1) Overdrive Pacing Algorithmsmentioning
confidence: 99%